All together groups and organizations. - Intelecom (Pasadena, Calif. : ntelecom, 2005)
"Whether a small group or a multinational corporation, every organization has its own culture. This lesson looks at organizational behavior and includes discussion around the ideas of Frederick Taylor and 'scientific management,' corporate culture and the pitfalls of bureacracy. As we see in the Outward Bound program, every organization has its own unique culture that is likened to the values and norms of the wider society."--from container.
Participants: Alan Levins, narrator.
DVD
No Master.
Keywords: Organizational behavior